Finding the Extraordinary in the Ordinary: Understanding the Role of Everyday Life in Coping With Health Challenges - Schrems, Berta (Nursing philosophy, 2025)
Theories of everyday life provide valuable insights into the experience of health and illness. Everyday life, as an essential part of social reality, is characterized by routines, familiarity, and practices that offer meaning, orientation, and security. However, its ordinariness also enables transformation, as disruptions caused by illness or social change necessitate adaptation and innovation. Nursing extends beyond medical treatment by considering how illness affects daily routines, relationships, and emotions. A theoretical framework of everyday life is particularly relevant in nursing, helping practitioners understand how people experience health, illness, and care. Acknowledging the role of daily living supports people in integrating health challenges into their routines and fosters person-centered care. Given the absence of a unified theory of everyday life, this study synthesizes concepts from various thinkers against empirical insights on health and illness. Philosophers such as Husserl, Heidegger, and Schütz highlight the importance of everyday preconceptions in interpreting life. They argue that individuals navigate challenges by relying on familiar patterns and adapting their experiences within daily life. In contrast, critical phenomenologists like Ahmed, Yancy, Salamon, and Al-Saji challenge this perspective, arguing that experience is shaped by social, political, and historical structures, including ethnicity, gender, class, and colonialism. In turn, theorists such as Lefebvre, Heller, and de Certeau emphasize everyday life as a dynamic space where repetition, creativity, and social relations intersect. Together, these approaches form a foundation for understanding the significance of everyday life. The synthesis of these theories with empirical findings underscores that everyday life plays a crucial role in coping with health and illness. It provides stability and orientation while enabling change, making it both a source of security and a space for transformation. This dual role of everyday life can be leveraged in nursing care to support people in managing illness and adapting to health challenges.